Sheep faeces decomposition and nutrient release across an environmental gradient in Southern Patagonia - Bahamonde, Héctor Alejandro; Gargaglione, Veronica Beatriz; Peri, Pablo Luis (2018)
In Southern Patagonia, most of the land ranging from the mountains to the sea in contrasting environmental conditions is devoted to extensive sheep farming. Existing estimations indicate that in ecosystems under livestock use, around 85% of the nitrogen (N) returning to the soil is through animal feces and urine. However, there is a lack of information concerning the rate of nutrient return into the soil from animal feces in Southern Patagonia. In this study, we evaluated the rate of sheep faeces decomposition and nutrient (N, P, Ca and K) release in three different ecological areas of Southern Patagonia, representing a West to East environmental gradient. Samples of fresh sheep dung were collected in the field, processed in the laboratory and located in three ecological areas and subsequently collected periodically during 820 days. The remaining organic matter (OM) of decomposing faeces did not vary between the three ecological areas. At the end of the trial (820 days), the rate of OM decomposition averaged 63% of the initial amount. According to the linear regressions performed, the time to reach 100% OM decomposition fluctuated between 3.7 and 4.2 years. Nutrient dynamics followed a common general trend, since nutrients were released during the first stages of decomposition, and then, fluctuations between nutrient immobilisation and release were observed. The prevailing environmental conditions among the ecological areas evaluated did not seem to involve a measurable effect on sheep faeces decomposition and nutrient release. The results obtained in this work may be useful for quantifying the return of organic matter and nutrients from sheep faeces to the soil in Southern Patagonia.